2015
DOI: 10.1016/j.celrep.2015.04.028
|View full text |Cite
|
Sign up to set email alerts
|

The SLC7A7 Transporter Identifies Microglial Precursors prior to Entry into the Brain

Abstract: During development, macrophages invade organs to establish phenotypically and transcriptionally distinct tissue-resident populations. How they invade and colonize these organs is unclear. In particular, it remains to be established whether they arise from naive equivalents that colonize organs randomly or whether there are committed macrophages that follow pre-determined migration paths. Here, by using a combination of genetics and imaging approaches in the zebrafish embryo, we have addressed how macrophages c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 47 publications
3
45
1
Order By: Relevance
“…These 2,411 genes included mpeg1 , on which FACS sorting was based, and other genes previously described in zebrafish microglia including apoeb , csfr1a , spi1a , slc7a7 and irf8 (Fig. E, Supporting Information Table S1) (Herbomel, Thisse, and Thisse, ; Rossi et al, ; Shiau et al, ; Svahn et al, ). In contrast, genes mostly expressed in neurons ( snap25a , neurod1 ), oligodendrocytes ( plp1a , mag ) and radial glia (s lc1a2b , s100b ) were significantly higher expressed in the GFP − neuronal and glia fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2,411 genes included mpeg1 , on which FACS sorting was based, and other genes previously described in zebrafish microglia including apoeb , csfr1a , spi1a , slc7a7 and irf8 (Fig. E, Supporting Information Table S1) (Herbomel, Thisse, and Thisse, ; Rossi et al, ; Shiau et al, ; Svahn et al, ). In contrast, genes mostly expressed in neurons ( snap25a , neurod1 ), oligodendrocytes ( plp1a , mag ) and radial glia (s lc1a2b , s100b ) were significantly higher expressed in the GFP − neuronal and glia fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as only a handful of zebrafish microglial genes are currently known, it is unknown how zebrafish microglia compare with mammalian microglia at the gene expression level (Herbomel, Thisse, and Thisse, ; Rossi et al, ; Shiau et al, ; Xu et al, ). To identify genome‐wide gene expression in microglia we optimized acute isolation of microglia from zebrafish brains by FACS and used RNA sequencing to compare their gene expression signature to the expression profile of other brain cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral red is a vital dye that accumulates in the lysosomes of microglia in living zebrafish larvae (Herbomel et al, 2001), and neutral red staining has been used to identify zebrafish mutants with abnormal microglia in our laboratory and others (e.g. Shiau et al 2013; Rossi et al 2015). Genetic mapping revealed that st77 and st74 define two different genes on chromosomes 14 and 4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…2A, B); apoe , which is a specific marker of microglia in zebrafish (Fig. 2C, D); and slc7a7 , which defines a restricted sub-population of macrophages and is necessary for microglia formation (Peri and Nüsslein-Volhard, 2008, Ellett et al, 2011, Rossi et al, 2015) (Fig. 2E, F).…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous factors that regulate microglial migration in the developing zebrafish. Cell autonomous factors, such as the Leucine/Arginine transporter, slc7a7 (Rossi et al, ), phosphate exporter XPR1 orthologue, xpr1b (Meireles et al, ), and noncanonical NOD‐like receptor, nlrc3‐like (Shiau et al, ), are required for primitive macrophage migration to and colonization of embryonic neuroepithelial tissues. Zebrafish slc7a7 , xpr1b , and nlrc3‐like mutants all lack microglia (Shiau et al, ; Meireles et al, ; Rossi et al, ,b), although the embryonic retinal and brain phenotypes among these mutants remain to be determined.…”
Section: Discussionmentioning
confidence: 99%